Urban Food Deserts: Perspectives from the Global South - Crush, Jonathan; Si, Zhenzhong (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The industrialization of the urban food system, alongside the proliferation of supermarkets, has dramatically transformed the landscape of food accessibility in cities. In many countries, the spatial consolidation of food provisioning has deprived many urban neighbourhoods of easy access to food, particularly foodstuffs integral to a healthy diet. These often socioeconomically disadvantaged urban areas are referred to as "food deserts". However, studies of urban food deserts in cities of the Global South are sparse, given their complicated urban food systems with the strong presence of informal food economies and diverse food sources. This book draws on empirical studies from South African, Brazilian and Chinese cities to investigate the food desert narrative, the characteristics of urban food environment and the various socioeconomic factors shaping it, as well as the food security and health consequences of urban food deserts. These studies reveal the limitations of applying the food desert concept to cities in the Global South and call for more holistic measurements of urban food insecurity.